La simulación de negocios como estrategia pedagógica / Business simulation as a pedagogical strategy - Pérez, Jeffery; González, Agustín (Cuaderno de Pedagogía Universitaria, 2014)
Se presenta un proyecto pedagógico sobre la simulación de negocios como estrategia pedagógica para mejorar el proceso de enseñanza-aprendizaje en la carrera de Administración de Empresas de la Pontificia Universidad Católica Madre y Maestra. El proyecto se desarrolló en dos asignaturas en paralelo, Estrategia Competitiva y Preparación y Evaluación de Proyectos. Se pretende que este estudio sirva de base para la toma de decisiones pedagógicas en el Departamento. Abstract This article presents an educational research regarding business simulation as a pedagogical strategy aimed to improve the teaching-learning process in Business Administration Studies at the Pontificia Universidad Católica Madre y Maestra. The authors based their initiative on the premise that this strategy could promote entrepreneur skills among Business Administration students. The study was developed in two parallel courses and analyzed the compiled data related to simulation and entrepreneurism. This study intends to act as groundwork that could lead to and inform pedagogical decisions at the Department.